2021
DOI: 10.2147/ndt.s317803
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis of the Prevalence and Determinants of Mental Distress Among Ethiopian Returnees

Abstract: Background: Returning internally displaced persons (IDPs) to their homes can be a difficult and traumatic experience, particularly after a long period of displacement. Furthermore, traumatic experiences encountered during displacement during the flight process may be replayed in the minds of IDP returnees when they return to their original locations, raising the risk of re-traumatization. This could have a detrimental impact on the mental health of returning IDPs. Despite this, the mental health of returnee ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…Those IDP who faced any type of trauma during displacement were six times more likely had PTSD than those who did not experience trauma (AOR = 6.00 [95% CI: 2.75–13.10]). This finding is similar with a study conducted in southern Ethiopia, which found that cumulative trauma was significantly associated with PTSD [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Those IDP who faced any type of trauma during displacement were six times more likely had PTSD than those who did not experience trauma (AOR = 6.00 [95% CI: 2.75–13.10]). This finding is similar with a study conducted in southern Ethiopia, which found that cumulative trauma was significantly associated with PTSD [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Internally displaced people who were unemployed had PSTD twice as compared to their counterparts (AOR = 2.09 [95% CI: 1.24–3.54]). This finding is relatively similar to other studies conducted in Ethiopia, which showed that unemployed people were twice as likely to suffer from mental distress as compared to the employed people [ 23 ]. This similarity might be because most of the study participants were farmers who spent much of their time in the fields and currently have nothing to do all-day.…”
Section: Discussionsupporting
confidence: 90%